The Effect of Work Environment, Work Safety, Reward and Punishment on Employee Performance of PT. Haleyora Powerindo Batam - Hanivah, Wydia; Yona, Mira; Zulhidayat, Zulhidayat; Sari, Hartika; Manalu, Puan Jelina; Syakinah, Syakinah; Widyanti, Rahmi (International Conference on Business Management and Accounting, 2024)
This study aims to determine the performance of employees of PT. Haleyora Powerindo Batam related to the work environment, work safety, rewards, and punishments. Employee performance (Y) is the dependent variable in this study. Workplace (X1), work safety (X2), rewards (X3), and punishments (X4) are independent variables in this scenario. A sample of 120 respondents was selected using a purposive sampling approach, and the population used in this study consisted of all 172 workers of PT. Haleyora Powerindo Batam. The multiple linear regression analysis approach used SPSS 25.0 software, and the research methodology was descriptive and quantitative. The research findings show that at PT. Haleyora Powerindo Batam, several variables significantly improve staff performance. The R Square value for reward and punishment factors that affect performance is 20.4%.